The game audio tutorial : a practical guide to sound and music for interactive games - Stevens, Richard; Raybould, Dave (Amsterdam ; Boston : Focal Press/Elsevier, 2011)
Basic training -- How big is the truck? -- Making it sound real -- Music systems -- Dialogue -- Making it sound good -- Advanced sound system design -- Next steps
Includes bibliographical references (p. 413-415) and index
IT
Keywords: Video games -- Sound effects; Computer game music; Computer sound processing; Sound -- Recording and reproducing -- Digital techniques